(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article explores the challenges and effective practices in fostering linguocultural competence among Korean language learners. Linguocultural competence involves understanding both the language and cultural context, a skill that is crucial for students aiming to communicate authentically in Korean. The article highlights common obstacles, such as difficulties in grasping cultural nuances, limited access to authentic cultural materials, and lack of intercultural interaction opportunities. To address these challenges, it examines practical strategies that enhance learning outcomes, including the use of multimedia resources, role-playing activities, and collaborative projects with native speakers. Emphasis is placed on the role of educators in creating a culturally inclusive environment that encourages critical thinking and empathy. By combining traditional and modern pedagogical approaches, this study provides educators with insights to effectively support Korean language learners in their journey toward linguocultural competence.